Neef, Rainer and Manuela Stanculescu (eds.) The Social Impact of Informal Economies in Eastern Europe. Aldershot: Ashgate, 2002 - РадаевВадим Валерьевич (Journal of Economic Sociology, 2010)
Detailed description in the text